ANALISIS RASIO LIKUIDITAS DAN PROFITABILITAS DALAM MENGUKUR KINERJA KEUANGAN PERUSAHAAN PADA PT TRIKOMSEL OKE Tbk PERIODE 2020-2024 - Ardhana, Muhammad Anugrah; Edy, Khairunnisa; Wulan, Wulan; Letisya, Andi Zivana; Parinding, Melzhianti; Supri, Baharman (Universitas Ichsan Sidenreng Rappang, 2025)
This study aims to analyze liquidity and profitability ratios in measuring the financial performance of PT Trikomsel Oke Tbk for the period 2020–2024. This research is a quantitative study using secondary data obtained from the company's annual financial statements accessed through the official website of the Indonesia Stock Exchange (www.idx.co.id). The analytical method used is financial ratio analysis, including Current Ratio, Quick Ratio, and Cash Ratio for liquidity, as well as Net Profit Margin, Return on Assets, and Return on Equity for profitability. The results show that the financial performance of PT Trikomsel Oke Tbk during the study period tended to fluctuate and was below the industry standard for both liquidity and profitability ratios. This indicates inefficiencies in asset utilization and the company's ability to meet short-term obligations. These findings are expected to provide input for the company's management in formulating strategies to improve financial performance.